Preventive cognitive protection based on AAV9 overexpression of IGF1 in hippocampal astrocytes - Peralta, Facundo (2024)
Astrocytes play key roles in the brain. When astrocyte support fails, neurological disorders follow, resulting indisrupted synaptic communication, neuronal degeneration, and cell death. We posit that astrocytes overexpressingneurotrophic factors, such as Insulin Like Growth Factor 1 (IGF1), prevent the onset ofneurodegeneration.We overexpressed IGF1 and the reporter TdTomato (TOM) in hippocampal astrocytes with bicistronic Adeno-Associated Virus (AAV) harboring the Glial Fibrillary Acidic Protein (GFAP) promoter and afterwards inducedneurodegeneration by the intracerebroventricular (ICV) injection of streptozotocin (STZ), a rat model ofbehavioral impairment, neuroinflammation and shortening of hippocampal astrocytes. We achieved a thoroughtransgene expression along the hippocampus with a single viral injection. Although species typical behavior wasimpaired, memory deficit was prevented by IGF1. STZ prompted astrocyte shortening, albeit the length of thesecells in animals injected with GFP and IGF1 vectors did not statistically differ from the other groups. In STZcontrol animals, hippocampal microglial reactive cells increased dramatically, but this was alleviated in IGF1rats.We conclude that overexpression of IGF1 in astrocytes prevents neurodegeneration onset. Hence, individualswith early neurotrophic exhaustion would be vulnerable to age-related neurodegeneration.